2015
DOI: 10.5194/bgd-12-231-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High variability of dissolved iron concentrations in the vicinity of Kerguelen Island (Southern Ocean)

Abstract: Abstract. Dissolved Fe (dFe) concentrations were measured in the upper 1300 m of the water column in the vicinity of Kerguelen Island as part of the second Kerguelen Ocean Plateau compared Study (KEOPS2). Concentrations ranged from 0.06 nmol L−1 in offshore, Southern Ocean waters, to 3.82 nmol L−1 within Hillsborough Bay, on the north-eastern coast of Kerguelen Island. Direct island runoff, glacial melting and resuspended sediments were identified as important inputs of dFe that could potentially fertilize the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 63 publications
(87 reference statements)
5
29
0
Order By: Relevance
“…5) due to high pFe and pAl supply over the Kerguelen Plateau that is relatively deficient in pMn, such as would be found in glacial runoff that has a signature which reflects fresh weathering of basaltic rocks (Doucet et al, 2005). This source theory is supported by the observation of high dissolved Mn (dMn) near the Leclaire Rise (Quéroué et al, 2015) and uniquely high pMn : pFe in sediments found below station R-2 (Table 2). Surface water particulate trace metals also reveal distinct differences.…”
Section: Elemental Ratios At Stations R-2 F-l and A3supporting
confidence: 67%
See 1 more Smart Citation
“…5) due to high pFe and pAl supply over the Kerguelen Plateau that is relatively deficient in pMn, such as would be found in glacial runoff that has a signature which reflects fresh weathering of basaltic rocks (Doucet et al, 2005). This source theory is supported by the observation of high dissolved Mn (dMn) near the Leclaire Rise (Quéroué et al, 2015) and uniquely high pMn : pFe in sediments found below station R-2 (Table 2). Surface water particulate trace metals also reveal distinct differences.…”
Section: Elemental Ratios At Stations R-2 F-l and A3supporting
confidence: 67%
“…Trace metal analysis of suspended particles, underlying sediment and settling particulate material will elucidate the source to sink progression of the particulate Fe pool. Following on from this work, and together with dissolved Fe measurements (Quéroué et al, 2015), a focused Fe budget will be constructed .…”
Section: Introductionmentioning
confidence: 99%
“…4b) and coincided with a slight increase in nutrients. There a deep Fe-enriched and lithogenic silica reservoir seemed to influence the area Quéroué et al, 2015). O 2 distribution was similar to that observed in the TEW.…”
Section: Biogeochemical Variablessupporting
confidence: 57%
“…Unexpectedly, the highest DWA Ba xs value of the whole study area (572 pM; 150-400 m) was observed at the reference R-2 site. For R-2, Bowie et al (2014), Quéroué et al (2015) and van der Merve et al (2015) reported local maxima in particulate and dissolved trace metals at 500 m and deeper, reflecting lateral transport of lithogenic matter possibly originating from the Leclaire Rise (a large seamount located west of R-2). Similarly, observed a maximum of lithogenic silica (LSi) at 500 m, confirming lithogenic inputs there.…”
Section: Depth-weighted Average Ba Xs Content Of Mesopelagic Watersmentioning
confidence: 99%
“…The R-2 HNLC reference station (white dot in Fig. 1b) is characterized by a very low biomass (with low iron contents; Quéroué et al, 2015). Stations TEW-3 and TNS-8 (black dots) are characterized by low to moderate biomass and Fe contents.…”
Section: Study Areamentioning
confidence: 99%